A novel aquaporin Aagp contributes to Streptococcus suis H2O2 efflux and virulence - Xinchi Zhu; Shuoyue Wang; Yu Du; Zijing Liang; Huochun Yao; Xiang Chen; Zongfu Wu (Virulence)
Streptococcus suis is a bacterium that can cause infections in pigs and humans. Although oxidative stress is common occurrence during bacterial growth and infection, the regulation networks of S. suis under oxidative stress remain poorly understood. To address this, we utilized RNA-Seq to reveal the transcriptional landscape of S. suis in response to H2O2 stress. We identified novel genes responsible for S. suis resistance to oxidative stress, including those involved in DNA repair or protection, and essential for the biosynthesis of amino acids and nucleic acids. In addition, we found that a novel aquaporin, Aagp, belonging to atypical aquaglyceroporins and widely distributed in diverse S. suis serotypes, plays a crucial role during H2O2 stress. By performing oxidative stress assays and measuring the intracellular H2O2 concentrations of the wild-type strain and Aagp mutants during H2O2 stress, we found that Aagp facilitated H2O2 efflux. Additionally, we found that Aagp might be involved in glycerol transport, as shown by the growth inhibition and H2O2 production in the presence of glycerol. Mice infection experiments indicated that Aagp contributed to S. suis virulence. This study contributes to understanding the mechanism of S. suis oxidative stress response, S. suis pathogenesis, and the function of aquaporins in prokaryotes.